Global research hotspots and trends in oxidative stress-related diabetic nephropathy: a bibliometric study - Wang, Xiao-rong; Wu, Zeng; He, Tong-tong; Chen, Xiao-han; Jin, Xiao-fei; Zuo, Chun-yue; Yang, Shao-ze; Gao, Yu; Zhou, Xiao-hong; Gao, Wei-juan (Frontiers in Endocrinology, 2025)
BackgroundOxidative stress is widely acknowledged as a key pathogenic mechanism in diabetic nephropathy (DN). In recent years, the role of oxidative stress in DN has garnered increasing attention. However, no bibliometric analysis has yet been conducted on the relationship between oxidative stress and DN. This study aims to systematically analyze the relevant literature, identify trends in research, assess current hotspots, and predict future directions.MethodsWe retrieved literature related to oxidative stress and DN from the Web of Science Core Collection database. We analyzed data on publication volume, countries/regions, institutions, journals, keywords, and other relevant metrics using VOSviewer, the Bibliometrix R package, and CiteSpace.ResultsFrom 2014 to 2024, a total of 4076 publications related to oxidative stress and DN were published across 755 journals, showing a consistent upward trend each year. China and the United States are the leading contributors in this field and demonstrate close collaborative efforts. The top contributors by country, institution, journal, and author include: China (1919 publications), Jilin University and Central South University (69 publications each), BIOMEDICINE & PHARMACOTHERAPY (117 publications), and Prof. Sun Lin (33 publications). The most frequent keyword is “oxidative stress” (3683 occurrences). In the co-citation analysis, Alicic RZ’s 2017 study was the most cited (144 citations). These findings highlight the critical importance of investigating the pathogenesis of DN from the oxidative stress perspective.ConclusionThis study demonstrates a steady increase in research on oxidative stress in DN since 2014, highlighting its central role in the pathogenesis of DN. Future research should focus on the molecular mechanisms of oxidative stress in DN and explore its therapeutic potential, to provide new strategies for the prevention and treatment of DN.